PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN DI HOTEL INDRAPURA PEKANBARU - Fitri, Yulita; Hendriani, Susi; Amsal, Chairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted at Indrapura Hotel Pekanbaru in Pekanbaru No.86 at Soetomo street road that aims to determine how Effect of compensation and working environment either simultaneously or partially on job spirit employee at Indrapura Hotel Pekanbaru. The population in this study were all full-time employees Indrapura Hotel Pekanbaru. Sampling was done by making the overall population of respondents ie 59 people. Source data from the primary data and secondary data. Data collection techniques in this study was through questionnaires and interviews. The analytical method used is descriptive quantitative method using multiple linear regression with SPSS version 19.00. Simultaneous regression test (F test) showed that the independent variables simultaneously compensation and working environment has a significant influence on job spirit employees. The magnitude of the effect that the coefficient of determination (R2) by the two variables simultaneously on the dependent variable while the remaining 79.3% 20.7% influenced by other variables not examined. Partial regression results (t test) showed that the dependent variable has an job spirit employees a significant effect on each of the independent variables studied were compensation and working environment.Keywords: Compensation, Working Environment, and Job Spirit Employee.